Adapting to (co)exist: experience of men with hemophilia in southern Brazil - Aline Machado Feijó; Eda Schwartz; Carme Ferré-Grau; Bianca Pozza dos Santos; Fernanda Lise (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective To understand the experience of men in relation to the process of living with hemophilia. Method Qualitative study using the theoretical and methodological referential Symbolic Interactionism and the constructivist strand of Grounded Theory. Participated 12 men with hemophilia followed at a Blood Center in the south of Rio Grande do Sul, Brazil. Intensive interviews, genograms and field notes were used for data collection, with concomitant analysis, following the initial, focused, and theoretical coding stages. Results The theoretical model was built, which has as central category Adapting to (co)exist with hemophilia and the categories Knowing yourself and the illness: knowing how to deal, Adjusting life: taking care of yourself and Getting used to the illness: being almost normal. Conclusion It was revealed the experience of men who adapt to (co)exist with hemophilia and their actions and behaviors, aiming to preserve them away from bleeding, pain, and the risk of death.